Group identity in markets - Li, Sherry Xin; Dogan, Kutsal; Haruvy, Ernan (International journal of industrial organization, 2011)
We present a laboratory experiment that measures the effects of group identity—one's perceived membership in social groups—on market transactions in an oligopoly market with a few sellers and buyers. We artificially induce group identity using art preferences and college majors in different treatments, respectively. Subjects are randomly assigned into the roles of buyers and sellers and interact repeatedly. We find that the presence of groups influences both the selection of trading partners and the determination of prices. All else equal, sellers are more likely to make offers to ingroup buyers, and the buyers are more likely to accept offers from ingroup sellers. There are considerable intergroup price differentials with the outgroup sellers charging a lower price than the ingroup sellers.